Sustainable strength improvement of soft clay stabilized with two sizes of recycled additive - Al-Bared, M.A.M. (GEOMATE International Society, 2018)
High amounts of ceramic waste is accumulated every year in the disposal and construction sites due to the rejection of all smashed, cracked, and broken tiles. The usage of recycled ceramic crushed tiles (RCT) in improving soft soil is considered an environmentally-friendly, economical and sustainable solution. Soft soils are characterized as problematic soils that are always associated with weak performance when loaded. It is a common practice to excavate, transport and dispose this kind of soil into landfills and replace it with a soil that meets the engineering requirements. Due to shortage of space in landfills and the high costs involved in this processes, soft soils are always treated at construction sites. In this study, two sizes of RCT (0.3 and 1.18 mm) are used to improve the physical and mechanical properties of soft soil. The size and percentage of RCT are investigated and its influence on unconfined compressive strength (UCS) and compaction is evaluated. Microstructural tests included scanning electron microscopic (SEM) and energy dispersive X-ray spectroscopy (EDS) were also conducted on samples treated with RCT. Noticeable increment in both density and unconfined compressive strength was achieved. The maximum dry density increased from 1.59 Mg/m3 to 1.82 Mg/m3 and 1.77 Mg/m3 at the addition of 40 1.18 mm and 0.3 mm RCT, respectively. Whereas the unconfined compressive strength increased from 50 kPa to 250 kPa and 225 kPa at 10 addition of 1.18 mm RCT and 40 0.3 mm RCT, respectively. The optimum value of RCT to treat soft clay was found to be 10 and 40 for 1.18 mm and 0.3 mm RCT, respectively. The remarkable improvement in the strength of soil is due to the development of cementation compounds that acts as a binder between the RCT and soil particles. This study would help in reducing the impacts created by disposing of both problematic soil and waste tiles. Besides, cement is the most traditional material used to stabilize soil. This research would contribute to reducing the CO2 produced during the production of cement. Â© 2018, Int. J. of GEOMATE.